Pengaruh Kualitas Pelayanan dan Pengalaman Belanja terhadap Kepuasan Pelanggan pada Tokma Kondang - Dadan Jaelani; Netti Nurlenawati; Dexi Triadinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tokma is a company operating in the retail sector. This research aims to analyze how much influence service quality and shopping experience have on customer satisfaction. This research uses a quantitative method, data collection is carried out by distributing questionnaires via Google Form to Tokma Kondang consumers. The data is then analyzed using multiple linear regression techniques and the sampling method applied is Accidental Sampling using the Lemesshow formula to determine the number of samples. The number of samples was 120 visitors to Tokma Kondang. The results of this research show that service quality positively and significantly influences customer satisfaction by 7,001, the correlation coefficient of shopping experience on customer satisfaction shows an influence of 10,180, the correlation coefficient of service quality and shopping experience on customer satisfaction is 201,089 and analysis of service quality and shopping experience simultaneously influence customer satisfaction by 77.1%